Pengelolaan Penilaian Autentik Kurikulum 2013Mata Pelajaran Matematika di SMA Negeri 2 Sukoharjo - Sandy, Gilang Ary, Prof. Dr. Sutama, M.Pd, Dr. Djalal Fuadi, M.M (2016)
Gilang Ary Sandy. Q 100140136. Management Of Authentic Assessment in Mathematic Curriculum 2013 At SMAN 2 ukoharjo. Sutama dan Djalal Fuadi. Thesis. Program Pascasarjana. Universitas Muhammadiyah Surakarta. 2016. The purpose of this study were (1) To describe the preparation of authentic assessment instrument mathematics. (2) Describe the implementation of authentic assessment mathematics. (3) Describe the utilization of authentic assessment mathematics. Qualitative research using case study design. Place of research on SMA Negeri 2 Sukoharjo. When the study of the month of February 2016 until the month of August 2016. The research subjects were the deputy head teacher of the school curriculum mathematics and students. Data collection techniques of interview, observation and documentation. Validation data by riangulation and source triangulation techniques. Data analysis with interactive techniques to process data reduction, data analysis and conclusion. The results of the study (1) Preparation of an assessment instrument performed by specifying aspects that will be investigated, formulate objectives, formulate indicators based on basic ompetencies, and make a minimum completeness criteria. (2) The attitude aspect assessment using observation and journals. Implementation aspects of knowledge is done with an oral test, written test and assignment. Test as an evaluation of the written test. Assignment is done by groups and individu. Implementation aspects of knowledge was done by using performance using a grading scale that accompanied the rubric. (3) The use of the results of the assessment to form positive attitudes of students, homogenize the thinking ability of students, provide information to parents, and improvements in the lesson plan.